2021
DOI: 10.24099/vet.arhiv.0857
|View full text |Cite
|
Sign up to set email alerts
|

A retroviral survey of endangered Eurasian lynx (Lynx lynx) from Croatia

Abstract: The feline immunodeficiency virus (FIV) and feline leukemia virus (FeLV) may cause persistent, lifelong and lethal infections in domestic and wild felids worldwide. FIV has been confirmed in most Felidae species, while FeLV infection is rare among non-domestic cats. The view that retroviruses are pathogenic in domestic cats but not in other free-ranging felid species was disproved by recent findings of retroviral pathology in several wild felids. The epidemiology of retroviral infections in felids in Croatia w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…The coronal suture was open in juveniles, partially closed in subadults, and fully closed in older adults. The sagittal crest in males of the subadult group was also comparably not developed, which was a characteristic of female adult specimens used for analysis 50 , 56 . Sexual dimorphism in the cranial structure became apparent through the progressive formation of ridges over time (see Supplementary Fig.…”
Section: Methodsmentioning
confidence: 95%
See 1 more Smart Citation
“…The coronal suture was open in juveniles, partially closed in subadults, and fully closed in older adults. The sagittal crest in males of the subadult group was also comparably not developed, which was a characteristic of female adult specimens used for analysis 50 , 56 . Sexual dimorphism in the cranial structure became apparent through the progressive formation of ridges over time (see Supplementary Fig.…”
Section: Methodsmentioning
confidence: 95%
“…These age-related alterations aligned with patterns observed in other species within the same genus, where there was a relative augmentation in the facial region of the skull alongside the emergence of postorbital compression 5 . In adult males, sagittal and occipital crests develop 50 , and the coronal suture is closed in both males and females. Based on these age criteria, we assigned 9 specimens to the juvenile group, 13 to the subadult group (up to 2 years for females and 3 years for males 5 ), and 32 to the adult group.…”
Section: Methodsmentioning
confidence: 99%
“…Our study revealed a significant difference between the total length of the fox (102.1 ± 4.8 mm) and jackal (117.7 ± 2.4 mm) mandibles, but this was similar to previous studies. Also, the total height of the vertical ramus was reported in two fox species as 3.7 ± 0.1 cm and 3.2 ± 0.2 cm (Munkhzull et al, 2018) in the golden jackal as 6.0 ± 0.58 cm (Monfared, 2013), in the lynx as 38.92 ± 1.63 mm, 44.1 ± 3.2 mm, (Gomerčić et al, 2010;Dayan et al, 2017) and in the wolf as 76.3 ± 3.8 mm (Okarma and Buchalczyk, 1993). The present study revealed similar values as in foxes from Mongolia (35.6 ± 2.2 mm), while the total height for the jackal was 42.6 ± 1.4 mm, which was significantly smaller compared with the study of jackals from Iran.…”
Section: Geometric Analysismentioning
confidence: 99%
“…2019), in golden jackals 11.2 ± 3.46 cm according to Monfared (2013). In other carnivores such as the lynx, the total length of the mandible was 102.6±5.2 mm according to Gomerčić (2010), 93.45 ± 2.98 mm according to Dayan et al (2017) and in the wolf 190.4 ± 7.7 mm according to Okarma and Buchalczyk (1993). Our study revealed a significant difference between the total length of the fox (102.1 ± 4.8 mm) and jackal (117.7 ± 2.4 mm) mandibles, but this was similar to previous studies.…”
Section: Geometric Analysismentioning
confidence: 99%
See 1 more Smart Citation